An evaluation of different material line insulators under high voltage AC and bipolar DC excitation in a marine polluted environment - Mouton, Gerton Nicolaas Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.